Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1097/mpg.0b013e31829d519a
|View full text |Cite
|
Sign up to set email alerts
|

Three Main Factors Define Changes in Fecal Microbiota Associated With Feeding Modality in Infants

Abstract: There is a clear clustering of components of infant microbiota based on the feeding method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…; however, effects of feeding on Lactobacillus abundance are inconsistent across other studies. Increased proportions of Lactobacillus, 25,26,48,54 as well as greater abundances of L. gasseri 28,47 in BF compared to FF infants have been reported, whereas other studies found opposite results 16,52,53 or reported intergroup variability and instability over time. 27,43 A greater prevalence 15 and higher proportion 24 and total counts 16,46 of C. difficile in FF compared to BF infants, as well as, significantly more Peptostreptococcaceae, 31 Akkermansia, 15 Veillonella, and Enterococcus 28 have been described.…”
Section: (Finland)mentioning
confidence: 62%
See 1 more Smart Citation
“…; however, effects of feeding on Lactobacillus abundance are inconsistent across other studies. Increased proportions of Lactobacillus, 25,26,48,54 as well as greater abundances of L. gasseri 28,47 in BF compared to FF infants have been reported, whereas other studies found opposite results 16,52,53 or reported intergroup variability and instability over time. 27,43 A greater prevalence 15 and higher proportion 24 and total counts 16,46 of C. difficile in FF compared to BF infants, as well as, significantly more Peptostreptococcaceae, 31 Akkermansia, 15 Veillonella, and Enterococcus 28 have been described.…”
Section: (Finland)mentioning
confidence: 62%
“…24,39,42 While many studies have focused on bifidobacterial colonization, breastfeeding supports other differences in microbiota composition. Within the phyla Bacteroidetes and Firmicutes, BF infants contain lower levels of Bacteroides, 33,50-53 Atopobium, 51,53 Clostridiales, Lachnospiraceae, and Faecalibacterium than FF. 33 Fan and colleagues 26 found that Bifidobacterium, Streptococcus, and Lactobacillus were dominant members in both feeding groups sampled between 3 and 6 mos; other dominant genera included Clostridium in BF infants and Klebsiella and Enterococcus in FF infants.…”
Section: (Finland)mentioning
confidence: 99%
“…Fecal samples were processed as previously described [16,17]. One gram of feces was homogenized in 9 mL of PBS (phosphate-buffered saline), and then 0.2 mL of the suspension was mixed with 0.6 mL of 4% paraformaldehyde (PFA) in PBS and fixed overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Their colonization after birth occurs through the vertical transfer of gut microbiota from the mother to the neonate [2,3] and is influenced by several factors [4] such as gestational age at birth [5], the mode of delivery [6], use of perinatal antibiotics [7], or the mode of feeding [8]. Recent studies have shown that one of the main sources of bifidobacteria is breast milk [9,10,11].…”
Section: Introductionmentioning
confidence: 99%